Plant-beneficial bacteria are promoted in pasture-crop rotations in the Uruguayan Pampa, contributing to soil health and crop performance - Cerecetto, Victoria; Smalla, Kornelia; Babin, Doreen; Leoni, Carolina (Frontiers in Bacteriology, 2025)
IntroductionUnderstanding how pasture-crop rotation design influences long-term soil health and microbial dynamics is crucial for sustainable agroecosystems. Pasture-crop rotations may alleviate soil degradation, but their long-term effects or legacy on soil and rhizosphere microbiomes, including potential recruitment of plant-beneficial microorganisms, and their link to crop yield need to be better understood. This study examines how land use intensity and grazed pasture legacy influence soil and rhizosphere prokaryotic diversity, composition, functionality, and crop productivity.MethodsA gradient of land use intensities ranging from continuous cropping (CCG), short (SR) and long (LR) pasture-crop rotations, permanent improved pasture (PIP), and natural grassland (NGL) were sampled in a long-term field experiment established in 1995 in the Uruguayan Pampa. Moreover, two stages of the rotation, one year after pasture sown with sorghum (SRS, LRS) and two years after pasture with soybean (SRG, LRG), were studied to assess the persistence of pasture-derived legacies. Soil physicochemical and biological properties were measured to evaluate soil health along with crop productivity. Bulk soil, soybean, and sorghum rhizosphere prokaryotic communities were analyzed across land use intensities using 16S rRNA gene amplicon sequencing and functional assays on rhizosphere bacterial isolates.ResultsResults showed a partial retention of soil health assessed through selected soil properties, i.e. soil organic C, total N, and soil extractable protein content were higher in LRG compared to CCG, while an intermediate response was observed in SRG. LR preserved the pasture legacy, maintaining bulk soil prokaryotic community composition similar to PIP and distinct from CCG, while SR converged to CCG and diverged from PIP. Soybean rhizosphere prokaryotic diversity and composition was strongly shaped by crop type and by soybean inoculation with Bradyrhizobium elkanii, overriding the effects of intensification and pasture legacy. Key soil taxa (Streptomyces, Solibacillus, Sphingomonas and Bradyrhizobium) were linked with improved soil functionality. Linking 16S rRNA gene sequencing data of rhizosphere taxa with rhizobacterial isolates showed that Pseudomonas, Bacillus, and Microbacterium, all exhibiting multiple plant-beneficial activities in vitro, were enriched in pasture rotations.DiscussionThis study highlights that pasture-crop rotation design, particularly pasture duration and plant composition, influences prokaryotic services and soil health, contributing towards the development of resilient agroecosystems.